The University of Iceland Joins Skemman - Áslaug Agnarsdóttir 1949- (2009)
Skemman (http://www.skemman.is) is an open access repository housing theses for four universities in Iceland. In February 2008 the University Council for the University of Iceland voted to join Skemman and collect electronic copies of students’ theses as well as paper copies. This article relates the process involved.